Isolation, morphological, and molecular characterization of a native Heterorhabditis indica strain from the Mid-Indian Himalayas with insights into biocontrol potential - Singh, Ashish Kumar; Patil, Jagadeesh; Nekkanti, Aarthi; Paschapur, Amit U.; Bhat, Sunaullah; Gouri, Vinita; Verma, Gaurav; Jaiman, Mukesh; Pankaj,; Mishra, K. K.; Kant, Lakshmi (Frontiers in Plant Science, 2025)
Entomopathogenic nematodes (EPNs) from the families Steinernematidae and Heterorhabditidae are biocontrol agents for the management of a wide range of insect pests. There is a tremendous opportunity for the discovery of new nematode strains and species adapted to local environmental conditions and insect pests. Therefore, in the present study, efforts were made to isolate EPN strains/species from the Northwestern Himalayas (NWH) region. The soil samples were collected from different locations in Almora, Uttarakhand. The collected soil samples were baited with Corcyra cephalonica, and they were observed regularly for their mortality. EPNs were isolated from the cadaver using the white trap method. Based on morphological and morphometrical studies, Heterorhabditis sp. VLEPN01 shows a resemblance to the species of Heterorhabditis indica. Further identity was confirmed with molecular characterization using the rDNA ITS marker. The sequence of this native EPN isolate revealed 99.87% similarity with H. indica isolated from Mizoram, Northeastern India (MF618314). The efficacy of EPN was evaluated against major insect pests of the NWH region. The results showed that H. indica VLEPN01 is capable of causing 100% mortality in fall armyworm (Spodoptera frugiperda), white grub (Anomala dimidiata), tobacco caterpillar (Spodoptera litura), and pod borer (Helicoverpa armigera) under laboratory conditions. Hence, H. indica VLEPN01 can be utilized for field testing in the management of insect pests occurring in the NWH region.